Evaluation of mimic defense strategy based on M-FlipIt game model - Shaohu DING; Ning QI; Yiwei GUO (Tongxin xuebao)
To make up for the lack of security performance evaluation of the mimic defense systems in the advanced persistent threat scenarios an improved game model based on the FlipIt game theory model was proposed.The dynamic strategy of mimic defense under different heterogeneity conditions was evaluated,and a case study for the simulation analysis was conducted.The simulation results show that the rotation of indefinite period can make up for the lack of heterogeneity and maintain the higher game payoff of defenders.